Alcohol production from sweet potato (Ipomoea batatas (L.) Lam.) genotypes in fermentative medium (2018)
Ethanol is one of the most promising fuels in Brazil, but its production is centralized in sugarcane cultivation, and is currently in search for other sources alcohol producing biomass to replace sugarcane monoculture. The aim of this study was to study fermentation process variables such as fermentation time (72 and 96 hours), addition of nutrients (with and without addition) and yeasts (dry and fresh organic yeast), employed in ethanol production from two sweet potato (Ipomoea batatas (L.) Lam.) genotypes: UGA 05 and UGA 77. Alcohol evaluation content in °GL was performed in a completely randomized design according to two factorial schemes (22 and 23), and results obtained were analyzed using Design Expert® software version 8. Results of the factorial design 22 indicate that fermentation time in alcohol production had a significant effect on the process, suggesting that alcohol production is more efficient in 72 hours of fermentation and without the inclusion of nutrients. In factorial design 23, the interactions between time of fermentation with genotypes and between time and inclusion of yeast showed significant effects and altered alcohol production. Fermentation process shows a significant difference as a function of genetic material and yeasts used pointing out fermentation of the flour must of genotype UGA 77 under fresh yeast action and 72 hours of fermentation.